Livestock stakeholder willingness to embrace preslaughter stunning in key Asian countries - Sinclair, Michelle; Idrus, Zulkifli; Burns, Georgette Leah; Phillips, Clive J. C. (MDPI, 2019)
Preslaughter stunning; the induction of unconsciousness and insensibility of animals prior to slaughter, is an important process for the welfare of livestock. The application of stunning is required by legislation in some countries, and rarely practised in others. In order to effectively advocate the implementation of stunning in the regions that do not include the practice as standard, it is first important to understand attitudes towards stunning, barriers to implementing stunning, and stakeholder willingness to embrace the practice. To this purpose, 17 focus group sessions were held with leaders in livestock production in China, Malaysia, Thailand, Vietnam, India and Bangladesh. Leaders were asked to rate their perceived willingness of livestock stakeholders to embrace stunning, and their rationales were discussed. In addition to this, the leaders were asked to present ideas to improve the willingness of stakeholders to embrace stunning. The data were qualitatively analysed used thematic analysis, quantified, and presented within this manuscript. Importantly, different attitudes and solutions existed by country, mostly in line with the predominating religion within the country, and the stage of economic development. Concerns around nonstatic and constantly evolving animal welfare benchmarks were also presented as important factors impacting the adoption of stunning, and the technical methods used. The findings of this study may aid in the development of programs that aim to increase the adoption of preslaughter stunning practices, to the purpose of improving animal welfare during slaughter.